Systematic review of assessment in undergraduate competency-based medical education and extrapolation of an assessment framework for Indian context - A study protocol - Sandeep K Gupta; Tripti Srivastava (Wolters Kluwer Medknow Publications, 2023)
There is a lack of studies that have systematically synthesized the existing literature related to the competency-based medical education (CBME) assessment process and identified gaps in existing knowledge about the assessment process structure. The aims of this study are as follows: 1. A systematic review of the assessment framework of CBME 2. Designing a model framework of assessment for CBME that will be relevant in the Indian context. The databases searched will be PubMed, MEDLINE (Ovid), EMBASE (Ovid), Scopus, Web of Science, and Google Scholar. General limits to the search will be set in the English language, published between January 2006 and December 2020, specific to competency-based education and assessment methods. After initial screening for duplicates and search limits, the title and abstract of the remaining studies will be screened. Subsequently, the full text of the articles will be screened against the inclusion and exclusion criteria for final selection. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flowchart of the systematic review will be used to describe the selection of the studies. The article quality will be assessed using the quality assessment tool for diverse study designs (QATSDD). The data synthesis will start with a descriptive summary (in tabular form) of the included studies. This study will try to provide comprehensive data to address challenges related to the CBME assessment process, which can help in evolving the robust assessment framework of CBME.